2012
DOI: 10.1007/s00436-011-2733-5
|View full text |Cite
|
Sign up to set email alerts
|

Blood parasites, body condition, and wing length in two subspecies of yellow wagtail (Motacilla flava) during migration

Abstract: Blood parasites of migrating yellow wagtails of two subspecies--Motacilla flava feldegg and Motacilla flava flava-were studied on a sample of 473 birds caught in spring and autumn periods in Bulgaria. We controlled eight "migration waves" (flocks captured in different evenings) of yellow wagtails for four parameters--average body mass, average fat level, average wing length, and average prevalence of different hematozoan species. Gametocytes or meronts of a total of six species of hematozoa belonging to three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 27 publications
1
23
0
Order By: Relevance
“…Plasma CORT sampled during migration reflects short-term modulation of hormone levels and suppressed responses to environmental stressors to facilitate resource mobilization necessary to fuel costly migration, independent of short-term changes in energetic conditions (Schwabl et al 1991;Holberton et al 1996;Romero et al 1997). We found no relationships between plasma and feather CORT, or parasite loads, which is perhaps a bit surprising, because parasites have been found to impose physiological stress and/ or increase energetic demands (Deviche et al 2001;Mougeot et al 2010;Shurulinkov et al 2012). However, like most trade-offs the effects of parasites on other life processes may only be apparent under compounding environmental stressors, like food shortages or poor health that create more variance in a population (Merino et al 2000;Tomas et al 2007;Mougeot et al 2010).…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Plasma CORT sampled during migration reflects short-term modulation of hormone levels and suppressed responses to environmental stressors to facilitate resource mobilization necessary to fuel costly migration, independent of short-term changes in energetic conditions (Schwabl et al 1991;Holberton et al 1996;Romero et al 1997). We found no relationships between plasma and feather CORT, or parasite loads, which is perhaps a bit surprising, because parasites have been found to impose physiological stress and/ or increase energetic demands (Deviche et al 2001;Mougeot et al 2010;Shurulinkov et al 2012). However, like most trade-offs the effects of parasites on other life processes may only be apparent under compounding environmental stressors, like food shortages or poor health that create more variance in a population (Merino et al 2000;Tomas et al 2007;Mougeot et al 2010).…”
Section: Discussionmentioning
confidence: 64%
“…; Shurulinkov et al. ). However, like most trade‐offs the effects of parasites on other life processes may only be apparent under compounding environmental stressors, like food shortages or poor health that create more variance in a population (Merino et al.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, in some cases, relationships between hematozoa infection and measures of body mass, body condition, and survival varied among hematozoa genera infecting birds and demographic characteristics of host populations including species, age, and sex (Schrader et al 2003;Ishak et al 2010;Lachish et al 2011;Rojo et al 2013;Meixell et al 2016). Other studies have found no relationship between hematozoa infection and bird growth (Shutler et al 1999b), wing length (Shurulinkov et al 2012), body mass (Bennett et al 1988;Shurulinkov et al 2012;Shutler et al 1999b), condition (Ashford 1971;Shurulinkov et al 2012;Sorensen et al 2016), or other health metrics (Shutler et al 1996(Shutler et al , 1999bStjerman et al 2004). Thus, targeted investigations are necessary to assess the effects of hematozoa infection on specific avian populations of interest.…”
Section: Introductionmentioning
confidence: 99%
“…Blood parasites of the genus Haemoproteus (Haemosporida, Haemoproteidae) are widespread in birds (Bensch et al 2009), and some of their species have been reported to affect bird fitness and even cause severe diseases both in avian hosts and blood-sucking insects (Marzal et al 2005;Ferrell et al 2007;Pacheco et al 2011;Shurulinkov et al 2012;Perkins 2014;Valkiūnas et al 2014a;Valkiūnas 2015). Sexual process and sporogony of avian haemoproteids occur in species of the Ceratopogonidae and Hippoboscidae, which transmit these pathogens (Atkinson et al 2008).…”
Section: Introductionmentioning
confidence: 99%